Tussen lokaal belang en wetenschappelijke ambitie: de publicatiegeschiedenis van Scientiarum Historia (1959-2006) - Vanpaemel, Geert (Studium, 2019)
Between local interest and scientific ambitions: the publication history of Scientiarum Historia (1959-2006). The Belgian journal Scientiarum Historia was founded in 1959 by Leon Elaut and Piet Boeynaems, and remained in print until 1975. It was taken up again in 1990 by the Belgian scholarly society Zuid-Gewina, and continued until 2006 when it was merged with other journals to form Studium. This paper discusses the background of its publication history, focusing on the strengths and weaknesses of a journal primarily devoted to local history. Among the weaknesses figure the limited financial support and the small community of readers and authors when working for a restricted local audience. However, it is argued that local history needs and deserves a special place in every historiography. The disappearance of Scientiarum Historia (and its successor, Studium) should cause concern about the fate of local historiography.